EXPLORING THE LATIN ROOTS OF CHEMICAL TERMINOLOGY: NAMES OF CHEMICAL ELEMENTS, ACIDS, AND OXIDES (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article explores how Latin has influenced chemical terminology, including element names, acids, and oxides. It highlights Latin roots in names like hydrogen, oxygen, and elements such as gold and uranium. Latin origins are also evident in acid names like hydrochloric and acetic acid, and oxide names like carbon dioxide. This influence adds historical depth to chemistry's language, connecting it to its linguistic roots.